2023
DOI: 10.1038/s41541-023-00665-3
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal COVID-19 vaccine induces respiratory memory T cells and protects K18-hACE mice against SARS-CoV-2 infection

Abstract: Current COVID-19 vaccines prevent severe disease, but do not induce mucosal immunity or prevent infection with SARS-CoV-2, especially with recent variants. Furthermore, serum antibody responses wane soon after immunization. We assessed the immunogenicity and protective efficacy of an experimental COVID-19 vaccine based on the SARS-CoV-2 Spike trimer formulated with a novel adjuvant LP-GMP, comprising TLR2 and STING agonists. We demonstrated that immunization of mice twice by the intranasal (i.n.) route or by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…Apart from the controversy surrounding whether intramuscular vaccination induces SARS-CoV-2 S-specific T RM cells in the airways, a growing body of evidence from animal models has demonstrated the superior ability of intranasal vaccination to induce airway T RM cells [ 143 , 148 , 149 , 150 ]. Therefore, innovative vaccines with different routes of administration are being developed, with a focus on inducing greater mucosal immunity that can provide durable protection at the site of infection.…”
Section: Adaptive Immunity To Sars-cov-2 Infection In the Airwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the controversy surrounding whether intramuscular vaccination induces SARS-CoV-2 S-specific T RM cells in the airways, a growing body of evidence from animal models has demonstrated the superior ability of intranasal vaccination to induce airway T RM cells [ 143 , 148 , 149 , 150 ]. Therefore, innovative vaccines with different routes of administration are being developed, with a focus on inducing greater mucosal immunity that can provide durable protection at the site of infection.…”
Section: Adaptive Immunity To Sars-cov-2 Infection In the Airwaymentioning
confidence: 99%
“…In a hamster model, the intranasal delivery of an adenovirus-based vaccine generated a robust neutralizing antibody response and provided better protection than intramuscular delivery [ 163 ]. Additionally, Diallo et al demonstrated that an intranasally delivered S protein trimer with adjuvant potently elicited S-specific IgG and IgA antibodies in the nasal cavity and lungs [ 150 ]. Collectively, these results indicate that vaccines capable of eliciting humoral responses in mucosal tissues may be effective strategies for inducing protective immunity.…”
Section: Adaptive Immunity To Sars-cov-2 Infection In the Airwaymentioning
confidence: 99%
“…1c). Immunization strategies such as nonconventional adjuvants [77,84], alternative antigen vectors [79,80,[85][86][87], or intranasal administration [78,[88][89][90] have all shown promise in providing superior immune protection of the nasal passages, though careful differential analysis of olfactory and respiratory tissues has not been performed. The exact signals that dictate protective OM plasma cell homing and protection remain to be precisely identified, but the discovery of the BOB has important implications for the design of vaccines that aim to protect the olfactory mucosa.…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…1c). Similarly, after vaccination, antigen-specific CD8 + and CD4 + T cells can migrate to the nasal passages and reside long term [87,103,104], limiting viral replication upon SARS-CoV-2 challenge [105]. These T cells have a repertoire that differs from that of circulating T cells, suggesting an independent and functionally distinct nasal T-cell response [103].…”
Section: Adaptive Immune Responsementioning
confidence: 99%
“…After vaccination with a Wuhan-Hu-1 derived DNA vaccine, both CD4+ and CD8+ T-cells were able to protect mice against Gamma or Omicron variants in the absence of significant levels of neutralising antibodies 11 . Intranasal vaccines have the potential to broaden the immune response and provide improved protection of mucosal surfaces by inducing local IgA and tissue-resident T-cell responses 12 . As our understanding of mechanisms of protection increases, efforts have also been directed toward understanding the efficacy of vaccine responses in individuals with co-morbidities.…”
mentioning
confidence: 99%